AAV vector encoding human VEGF165–transduced pectineus muscular flaps increase the formation of new tissue through induction of angiogenesis in an in vivo chamber for tissue engineering: A technique to enhance tissue and vessels in microsurgically engineered tissue. (7th December 2015) - Moimas, Silvia; Manasseri, Benedetto; Cuccia, Giuseppe; Stagno d'Alcontres, Francesco; Geuna, Stefano; Pattarini, Lucia; Zentilin, Lorena; Giacca, Mauro; Colonna, Michele R
In regenerative medicine, new approaches are required for the creation of tissue substitutes, and the interplay between different research areas, such as tissue engineering, microsurgery and gene therapy, is mandatory. In this article, we report a modification of a published model of tissue engineering, based on an arterio-venous loop enveloped in a cross-linked collagen–glycosaminoglycan template, which acts as an isolated chamber for angiogenesis and new tissue formation. In order to foster tissue formation within the chamber, which entails on the development of new vessels, we wondered whether we might combine tissue engineering with a gene therapy approach. Based on the well-described tropism of adeno-associated viral vectors for post-mitotic tissues, a muscular flap was harvested from the pectineus muscle, inserted into the chamber and transduced by either AAV vector encoding human VEGF165 or AAV vector expressing the reporter gene β-galactosidase, as a control. Histological analysis of the specimens showed that muscle transduction by AAV vector encoding human VEGF165 resulted in enhanced tissue formation, with a significant increase in the number of arterioles within the chamber in comparison with the previously published model. Pectineus muscular flap, transduced by adeno-associated viral vectors, acted as a source of the proangiogenic factor vascular endothelial growth factor, thus inducing a consistent enhancement of vessel growth into the newly formed tissue within the chamber. In conclusion, our present findings combine three different research fields such as microsurgery, tissue engineering and gene therapy, suggesting and showing the feasibility of a mixed approach for regenerative medicine.